Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome